2016
DOI: 10.7567/jjap.55.086502
|View full text |Cite
|
Sign up to set email alerts
|

SiN etching characteristics of Ar/CH3F/O2 plasma and dependence on SiN film density

Abstract: We evaluated the silicon nitride (SiN) etching characteristics of Ar/O2/hydrofluorocarbon plasma. Ar/CH3F/O2 plasma achieved a high etching selectivity of SiN to SiO2 by increasing the oxygen flow rate. We also evaluated the dependence of SiN etching characteristics on SiN film density. A low-density film deposited at a low temperature of 200 °C (by plasma-enhanced CVD, PECVD) showed an 8–20% lower etching rate of SiN than a high-density film deposited at a high temperature of 780 °C (by low-pressure CVD, LPCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The transfer of the PDMSB/SOC features into SiN was achieved with a Ar/CH 3 F/O 2 gas chemistry (Ar 200 sccm, CH 3 F 70 sccm, O 2 30 sccm, 10 mT, 400 Ws, 50 Wb). Other attempts with an Ar/CF 4 /CHF 3 plasma showed poor selectivity, limiting the depth of the transfer into SiN to approximately 20 nm before complete etching of the SOC mask.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of the PDMSB/SOC features into SiN was achieved with a Ar/CH 3 F/O 2 gas chemistry (Ar 200 sccm, CH 3 F 70 sccm, O 2 30 sccm, 10 mT, 400 Ws, 50 Wb). Other attempts with an Ar/CF 4 /CHF 3 plasma showed poor selectivity, limiting the depth of the transfer into SiN to approximately 20 nm before complete etching of the SOC mask.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous observations, where the etching conditions should favor sidewall passivation via the deposition of poorly volatile brominated etch products formed during SOC etching. 28 The transfer of the PDMSB/SOC features into SiN was achieved with a Ar/CH 3 F/O 2 gas chemistry 30 (Ar 200 sccm, CH 3 F 70 sccm, O 2 30 sccm, 10 mT, 400 Ws, 50 Wb). Other attempts with an Ar/CF 4 /CHF 3 plasma showed poor selectivity, limiting the depth of the transfer into SiN to approximately 20 nm before complete etching of the SOC mask.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has also been reported that high SiN/SiO 2 selectivity can be achieved using gas mixtures such as NF 3 /O 2 or CF 4 /N 2 /O 2 plasmas, which is attributed to the influence of NO radicals. , The addition of hydrogen to fluorocarbon gas, leading to the generation of CH x F y ions, can be used to enhance the etch rate (ER) and/or selectivity of SiN/SiO 2 or SiN/Si. Special hydrofluorocarbon gases have been used to achieve high etch selectivity for SiN over SiO 2 and Si. Additionally, the dependence of selectivities between Si-based materials on substrate temperature has recently been investigated by various research groups. , In hydrogen-contained fluorocarbon plasmas, the formation of hydrogen fluoride (HF) is anticipated to have a detrimental effect on etching for Si-based materials, as it tends to scavenge F radicals . In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. , Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas , On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. , …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] or hydrofluorocarbon C x H y F z (Refs. [7][8][9][10][11][12][13][14][15] chemistries. Fluorine-rich gases such as CF 4 , C 4 F 8 , or CHF 3 with a high Si 3 N 4 etch rate of about 30 nm min −1 were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,10,13,17 Oxygen helps to reduce the concentration of fluorocarbon radicals like CF x by forming volatile species such as CO, CO 2 , or COF 2 and enhance Si 3 N 4 etching. 9,10,18 Hydrogen from incident hydrofluorocarbon tends to increase the etching rate of Si 3 N 4 compared to fluorocarbon without hydrogen by the possible reaction of volatile species, such as HCN. 18,19 Moreover, it scavenges fluorine from the deposited film, reducing its fluorine content.…”
Section: Introductionmentioning
confidence: 99%